Comparative Physiological, Biochemical, and Genetic Responses to Prolonged Waterlogging Stress in Okra and Maize Given Exogenous Ethylene Priming - Vwioko, Emuejevoke; Adinkwu, Onyekachukwu; El-Esawi, Mohamed A. (Frontiers in Physiology, 2017)
Waterlogging is an environmental challenge affecting crops worldwide. Ethylene induces the expression of genes linked to important agronomic traits under waterlogged conditions. The ability of okra (Abelmoschus esculentus L. Moench.) and maize (Zea mays L.) given exogenous ethylene priming to tolerate prolonged waterlogged conditions was investigated in this study. The investigation was carried out as field experiments using 3 week-old plants grouped into 4 treatments; control, waterlogged plants, ethylene priming of plants before waterlogging, and ethylene priming of plants after waterlogging. Different growth parameters were recorded. Soil chemical and bacterial analyses were performed. The activity and gene expression of antioxidant enzymes were studied. The ethylene biosynthetic genes expression analysis and root anatomy of surviving okra plants were also carried out. Results revealed that okra and maize plants showed increase in their height under waterlogged conditions. Ethylene priming and waterlogged conditions induced early production of adventitious roots in okra and maize. Maize survival lasted between 5 and 9 weeks under waterlogging without reaching the flowering stage. However, okra survived up to 15 weeks under waterlogging producing flower buds and fruits in all treatments. Variable changes were also recorded for total soluble phenolics of soil. Cross sections of waterlogged okra roots showed the formation of a dark peripheral layer and numerous large aerenchyma cells which may have assisted in trapping oxygen required for survival. The activity and gene expression levels of antioxidant enzymes were studied and showed higher increases in the root and leaf tissues of okra and maize subjected to both waterlogging and ethylene priming, as compared to control or waterlogged condition. Quantitative RT-PCR analysis also showed that the ethylene biosynthetic gene expression levels in all okra and maize tissues were up-regulated and showed much higher levels under ethylene-treated waterlogged conditions than those expressed under control or waterlogged conditions at all time points. These results indicate that okra and maize tissues respond to the conditions of waterlogging and exogenous ethylene priming by inducing their ethylene biosynthetic genes expression in order to enhance ethylene production and tolerate the prolonged waterlogging stress. In conclusion, this study revealed that exogenously generated ethylene gas as